The Role of Gut Dysbiosis and Its Treatment in the Critically Ill - Rizzo, Toni (MD Conference Express, 2015)
Altered intestinal microbiota in critically ill patients leads to increased pathogens and infections, which may be improved with synbiotic therapy. Stress, antibiotics, and parenteral therapy have been linked to gut dysbiosis. Fecal microbiota transplantation is a promising treatment for Clostridium difficile infection and may work by altering bile acid composition.